TRANSFORMASI GERAKAN ISLAM POLITIK DALAM PARTAI POLITIK ISLAM : ANALISA KOMPARATIF AKP DAN PKS DI TURKI DAN INDONESIA - Akbar, M. Chairil; Mayrudin, Yeby Ma’asan; Narendra, Rosa Arista (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2018)
This study seeks to analyze the transformation of the political Islam movement carried out by the PKS (Prosperous Justice Party) and Justice and Development Party AKP (Adalet ve Kalkinma Partition), Turkey, by tracing the general pattern of similar strategies adopted by them, including differences that arise in both parties. PKS and AKP are major Islamic parties in the world that have so far successfully fought in electoral competitions. How to make use of their mass base and Islamic sentiment in liberal parliamentary struggle is a tactical step that characterizes the political Islam movement. Comparison will be made to find the common thread concerning Islamic-style populism with the electoral strategy they use. Political Islam can ultimately be understood not only from the categories of morality, ethics, or religion, but also on the objective category based on political realism.The authors believe that this theme is important and interesting after examining the development of identity political movements that have occurred not only in Indonesia but also in several other countries in the world in the last 10 years. Analysis of the AKP and PKS must, however, be understood in two aspects, namely, first, a cross-over between liberal democracy and Islamic activism, and secondly, the tendency to change the political strategy of the Islamic party. The interplay between the interests of electoral achievement and the ideological vision is a big and dynamic dilemma.Of the various methods available, the research team in this study used qualitative research methods. Data is obtained through a literature review or study of relevant literature such as books, journals, news websites, or thesis or dissertation works. The author's temporary hypothesis is that first, PKS and AKP have political linkage in three things, first, the political vision of Islam which is heavily influenced by the Muslim Brotherhood movement, second, the construction of civil networks and organizations, and the three, electoral strategies and compromise on liberal democracy. PKS and AKP are in turn conditioned by a number of compromises  and political pragmatism. Both are forced to adapt substantially in terms of changes in party models to be more open and plural. Thus, there is a convergence between political Islam and the flow of liberal democracy based on the typical political situation in Indonesia and Turkey. The differences that arise are the political Islam platform of AKP is significantly influenced by the trajectory of Islamic tradition which has long been rooted in the sociological pattern of its society and the economic platform of neoliberalism that has been adopted and applied aggressively by the AKP since its reign in Turkey.